Enhancing household food security through the secondary school agriculture student: the stakeholders’ perceptions in Kenya - Njura, Hellen Joseph; Kubai, Isaac (My University, 2026)
This study investigates stakeholders’ perceptions of the role of secondary school agriculture students in enhancing household food security. Despite extensive research on agricultural education and skills development, limited studies have explored how stakeholders perceive students’ specific roles as learners, innovators, trainers, informants and implementers of food security policy. Using descriptive and correlational designs, data were collected from 376 students, 111 agriculture teachers and 323 parents. Findings show that agriculture students play a significant role in promoting food security through learning, innovation and policy engagement yet, their participation is hindered by the absence of clear policy guidelines. Addressing this gap, the study proposes integrating practical food security initiatives into the secondary agriculture curriculum through experiential learning such as school gardens and community projects. It urges education policymakers, including KICD and the Ministry of Education to institutionalize student participation in food security initiatives, aligning school agriculture with national policies and strengthening cross-sector collaboration with the Ministry of Agriculture.
Articles
Keywords: Agriculture students; food security; secondary education; stakeholder perceptions; role; Curriculum Studies; Educational Research; Research Methods in Education; Secondary Education